CaMKII does not control mitochondrial Ca2+ uptake in cardiac myocytes - Nickel, Alexander; Kohlhaas, Michael; Bertero, Edoardo; Wilhelm, Daniel; Wagner, Michael; Sequeira, Vasco; Kreußer, Michael; Dewenter, Matthias; Kappl, Reinhard; Hoth, Markus; Dudek, Jan; Backs, Johannes; et al. (The journal of physiology, 2020)
Key points Mitochondrial Ca2+ uptake stimulates the Krebs cycle to regenerate the reduced forms of pyridine nucleotides (NADH, NADPH and FADH2) required for ATP production and reactive oxygen species (ROS) elimination. Ca2+/calmodulin-dependent protein kinase II (CaMKII) has been proposed to regulate mitochondrial Ca2+ uptake via mitochondrial Ca2+ uniporter phosphorylation. We used two mouse models with either global deletion of CaMKIIδ (CaMKIIδ knockout) or cardiomyocyte-specific deletion of CaMKIIδ and γ (CaMKIIδ/γ double knockout) to interrogate whether CaMKII controls mitochondrial Ca2+ uptake in isolated mitochondria and during β-adrenergic stimulation in cardiac myocytes. CaMKIIδ/γ did not control Ca2+ uptake, respiration or ROS emission in isolated cardiac mitochondria, nor in isolated cardiac myocytes, during β-adrenergic stimulation and pacing. The results of the present study do not support a relevant role of CaMKII for mitochondrial Ca2+ uptake in cardiac myocytes under physiological conditions. Abstract Mitochondria are the main source of ATP and reactive oxygen species (ROS) in cardiac myocytes. Furthermore, activation of the mitochondrial permeability transition pore (mPTP) induces programmed cell death. These processes are essentially controlled by Ca2+, which is taken up into mitochondria via the mitochondrial Ca2+ uniporter (MCU). It was recently proposed that Ca2+/calmodulin-dependent protein kinase II (CaMKII) regulates Ca2+ uptake by interacting with the MCU, thereby affecting mPTP activation and programmed cell death. In the present study, we investigated the role of CaMKII under physiological conditions in which mitochondrial Ca2+ uptake matches energy supply to the demand of cardiac myocytes. Accordingly, we measured mitochondrial Ca2+ uptake in isolated mitochondria and cardiac myocytes harvested from cardiomyocyte-specific CaMKII δ and γ double knockout (KO) (CaMKIIδ/γ DKO) and global CaMKIIδ KO mice. To simulate a physiological workload increase, cardiac myocytes were subjected to β-adrenergic stimulation (by isoproterenol superfusion) and an increase in stimulation frequency (from 0.5 to 5 Hz). No differences in mitochondrial Ca2+ accumulation were detected in isolated mitochondria or cardiac myocytes from both CaMKII KO models compared to wild-type littermates. Mitochondrial redox state and ROS production were unchanged in CaMKIIδ/γ DKO, whereas we observed a mild oxidation of mitochondrial redox state and an increase in H2O2 emission from CaMKIIδ KO cardiac myocytes exposed to an increase in workload. In conclusion, the results obtained in the present study do not support the regulation of mitochondrial Ca2+ uptake via the MCU or mPTP activation by CaMKII in cardiac myocytes under physiological conditions.
Accepted manuscipt online: 16 February 2019
Gesehen am 20.04.2020